First Female Travel Journalist Meets First Lady: Mary Pos and Eleanor Roosevelt Speak on Women’s Roles and Intercultural Understanding - Babs Boter (European Journal of American Studies)
Mary Pos, self-proclaimed first female travel journalist from the Netherlands, met Eleanor Roosevelt first in 1937 during a women-only press conference at the White House, and then in 1950 when Roosevelt visited Amsterdam. This essay examines Pos’ published and unpublished reports of these encounters in order to see which professional and psychological forces were at work in the transnational and gendered arena of journalism in the late 1930s and early 1950s. Secondly, it will investigate potential correlations between Roosevelt’s and Pos’ ideas on women’s rights and intercultural understanding.